2015
DOI: 10.5937/industrija43-8718
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between innovativeness and strategic planning: Empirical research

Abstract: This paper studies the relationship between innovativeness and strategic planning in SMEs.In introduction part, the authors attempt to consider relevant findings about this specific relationship in the literature. The paper presents how the EU policy approaches the innovation management system within SMEs and where Serbia stands in catching up the process towards the EU in terms of innovativeness and competitiveness. The main research approach is to examine the relationship between innovativeness and strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Also, large organizations which have a strategy focused on innovation enhance overall innovativeness (ρ = .311, Sig = .028), which is identical to the results of empirical research conducted by Mamula and Popović-Pantić (2015), who focused their attention on SMEs and reached the conclusion that: "SMEs with clearly defined innovation strategies achieved higher scores on all types of innovation as compared to SMEs that did not report having such a document" (2015, p. 59). Furthermore, encouraging staff toward creative thinking that results in new conceptual solutions in business processes, products and services directly lead to a higher degree of a firm innovativeness (ρ = .300, Sig = .034).…”
Section: Source: the Authors' Calculationsupporting
confidence: 71%
See 1 more Smart Citation
“…Also, large organizations which have a strategy focused on innovation enhance overall innovativeness (ρ = .311, Sig = .028), which is identical to the results of empirical research conducted by Mamula and Popović-Pantić (2015), who focused their attention on SMEs and reached the conclusion that: "SMEs with clearly defined innovation strategies achieved higher scores on all types of innovation as compared to SMEs that did not report having such a document" (2015, p. 59). Furthermore, encouraging staff toward creative thinking that results in new conceptual solutions in business processes, products and services directly lead to a higher degree of a firm innovativeness (ρ = .300, Sig = .034).…”
Section: Source: the Authors' Calculationsupporting
confidence: 71%
“…001), then the degree of firm innovativeness can be greatly enhanced. As mentioned above, earlier studies, as well as results, have shown that innovative companies with access to financial resources (Mamula & Popović-Pantić, 2015) can "invest in innovative activities and behave more innovatively" (Mamula & Popović-Pantić, 2015, p. 61;Mosurović & Kutlača, 2011) which improves overall firm innovativeness.…”
Section: Source: the Authors' Calculationmentioning
confidence: 90%
“…"When faced with a changing or uncertain business landscape, companies cannot resolve to playing by the same rules as their competitors" (Mamula, Popović-Pantić, 2015). As a rule, when there is the possibility of corruption, regardless of whether it takes place, not only must the protection of the procurers' rights be discussed, but also the protection of all parties involved in public procurement processes.…”
Section: Resultsmentioning
confidence: 99%
“…Cândido and Sousa (2017) find that those Brazilian SMEs that formalize their strategy are more likely to implement OI. While Mamula and Popovic-Pantic (2015) observe that Serbian SMEs with strategic planning can present successful innovation projects with greater confidence. If a firm proactively manages knowledge inflows and outflows, it can strategically leverage a multitude of new strategic options (Kutvonen, 2011).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%